Computerised cognitive–behavioural therapy for adults with intellectual disability: randomised controlled trial. (August 2017) - Cooney, Patricia; Jackman, Catherine; Coyle, David; O'Reilly, Gary
Abstract : Background: Despite the evidence base for computer-assisted cognitive–behavioural therapy (CBT) in the general population, it has not yet been adapted for use with adults who have an intellectual disability. Aims: To evaluate the utility of a CBT computer game for adults who have an intellectual disability. Method: A 2 × 3 (group × time) randomised controlled trial design was used. Fifty-two adults with mild to moderate intellectual disability and anxiety or depression were randomly allocated to two groups: computerised CBT (cCBT) or psychiatric treatment as usual (TAU), and assessed at pre-treatment, post-treatment and 3-month follow-up. Forty-nine participants were included in the final analysis. Results: A significant group x time interaction was observed on the primary outcome measure of anxiety (Glasgow Anxiety Scale for people with an Intellectual Disability), favouring cCBT over TAU, but not on the primary outcome measure of depression (Glasgow Depression Scale for people with a Learning Disability). A medium effect size for anxiety symptoms was observed at post-treatment and a large effect size was observed after follow-up. Reliability of Change Indices indicated that the intervention produced clinically significant change in the cCBT group in comparison with TAU. Conclusions: As the first application of cCBT for adults with intellectual disability, this intervention appears to be a useful treatment option to reduce anxiety symptoms in this population.